FACTORS OF TECHNOLOGICAL DEVELOPMENT AND RE-INDUSTRIALIZATION OF TRADITIONAL INDUSTRIAL SECTORS - O. A. Yeremchenko; O. V. Cherchenko (Ekonomika Nauki)
The factors contributing to the technological development of traditional sectors of industry, in particular the global automotive industry, are considered. It is noted that the automotive industry, which is not related to high-tech industries, by the end of 2017 entered the top 3 industries with the highest level of science among the six largest industrial sectors. The analysis of the competitive landscape and strategies of technological diversification of the traditional leaders of the automotive industry, caused by the emergence of technologies for the electrification of vehicles, was carried out. It is concluded that among the factors that lead to reindustrialisation traditional industries, are the emergence breakthrough technology; the escalation of competition for new niches formed by this technology; a sharp increase in the volume of budgets for research; increasing of investment and patent activity; removal of barriers established by intellectual property rights; cooperation with companies of related industries.